Principles of organizing an educational environment based on academic integrity - Bashkir, Olha; Druhanova, Olena (Educological discourse, 2026)
In modern educational institutions, efficiency contributes to the creation of a safe, flexible educational space that takes into account the psychological, physical and social needs of students and promotes their harmonious development. A fair educational environment, regulated by the Law of Ukraine ‘On Education’ (Article 42), ensures transparency in assessment, detection of plagiarism and corruption, and builds trust in learning outcomes and professional value. Based on a review of several scientific works devoted to the development and requirements of the educational environment and academic integrity, it has been established that an ethical educational environment in an educational institution is one in which all participants in the educational process systematically adhere to the principles of academic integrity (honesty, trust, fairness, respect, responsibility, courage to act), ensuring transparency of rules, fairness of assessment, respect for copyright, inadmissibility of corruption, plagiarism and other forms of dishonesty, which creates a basis for trust in learning outcomes and scientific achievements and guarantees the quality of education. The article identifies the fundamental principles for creating an ethical educational environment within an educational institution from the perspective of its environmental sustainability: the principle of humanization (unlocking the creative potential of students, protecting rights and freedoms, shifting communication from social roles to personal interaction, and ensuring the psychological well-being of teachers as a condition for effective work); the principle of dialogue (partner subject-subject interaction, where dialogue motivates learning and reduces stress); the principle of combining information and network technologies with interactive teaching methods (business games, the POPS formula, Six Thinking Hats, the case method, storytelling; tools such as Story Dice, Padlet, Nearpod, etc.; replacement of direct contacts with network communications in wartime, development of cognitive skills and socialisation, creation of an expert and project environment, activation of reflection and a competence-based approach; the principle of safety and psychological comfort (protection from violence, bullying, conflicts; confidence, stability, morality, positive worldview, unlocking potential for self-development).